A novel stainless steel fiber felt/Pd nanocatalysts electrode for efficient ORR in air-cathode microbial fuel cells. (20th November 2019) - Chen, Wenwen; Liu, Zhongliang; Li, Yanxia; Jiang, Kejun; Hou, Junxian; Lou, Xiaoge; Xing, Xiaoye; Liao, Qiang; Zhu, Xun
Abstract: A 3D macroporous stainless steel fiber felt (SSFF) is used as base material and a simple water bath method is adopted to directly load Pd nanocatalysts on SSFF to fabricate the air cathode of microbial fuel cells (MFCs). The optimum Pd loading is explored on the basis of the optimized PVP additive amount and reaction temperature. To attain a high ORR activity, a conductive carbon black filling layer is added into the 3D pores of Pd-SSFF. A series of physical and electrochemical tests are conducted to characterize the morphology, chemical composition and oxygen reduction activity and then the obtained cathodes are installed in MFCs for electricity production verification. The results show that the Pd-SSFF cathode at a Pd loading of 0.5 mg cm −2 (Pd-SSFF-0.5) achieves high output voltage and power density (492.65 mV, 390.79 mW m −2 ) which are comparable to the conventional Pt/C electrode (504.80 mV, 405.47 mW m −2 ). Furthermore, with Pd-SSFF-0.5 cathode the high-voltage platform duration of MFC in one operation cycle is 2.79 times of that of Pt/C electrode. Excellent mechanical properties (high pressure and corrosion tolerance), high electric energy output and simple fabrication prove it is an efficient strategy to improve the overall performance of MFCs using the obtained cathodes. Highlights: 3D macroporous SSFF is proposed as base material in air cathode. Pd nanocatalysts is loaded directly on SSFF with the simple water bath method. This loading method can replace the complex preparation process of powder catalysts. Filling carbon black into the 3D pores of Pd-SSFF helps improving ORR performance. Excellent mechanical properties and high electric output are achieved by Pd-SSFF cathodes.